Evaluation of effectiveness of 10% polyvinylpyrrolidone-iodine solution against infections in wire and pin holes for Ilizarov external fixators - Camilo, Adelina Morais; Bongiovanni, José Carlos (São Paulo Medical Journal, 2005)
CONTEXT AND OBJECTIVE: Superﬁcial infection at wire and pin insertions in the skin is a frequent disorder among patients utilizing the Ilizarov method. The objective of this study was to evalu- ate the effectiveness of daily topical application of 10% polyvinylpyrrolidone-iodine solution against infections of the holes for Kirschner wires and Schanz pins among patients using Ilizarov external ﬁxators, in comparison with cleaning these holes only with 0.9% sterile physiological saline solution. DESIGN AND SETTING: Controlled randomized clinical trial, in the Orthopedics and Traumatology Outpatient Clinic, Hospital São Paulo, and Ortho- pedics and Traumatology Center of Jundiaí. METHODS: 30 patients were treated using the Ilizarov technique: 15 were instructed to apply 0.9% physiological saline dressing on the wire and pin insertions and 15 to apply 0.9% physiological saline plus 10% polyvinylpyr- rolidone-iodine. Patients were evaluated at outpatient return visits for identiﬁcation of signs and symptoms of superﬁcial infection at wire and pin insertion sites. Samples were collected from cases of purulent exudate secretion, for culturing and clinical tests. RESULTS: The chi-squared and Fischer exact tests were applied, but no statistically signiﬁcant association between the intervention of topical polyvinylpyrrolidone-iodine solution and the prevention of infections at wire and pin insertions could be found. CONCLUSIONS: Topical 10% polyvinylpyrrol- idone-iodine solution applied daily to Kirschner wire and Schanz pin insertions did not reduce the incidence of superﬁcial infection at these holes, in comparison with mechanical removal of dirt using 0.9% physiological saline solution.